Analisis penerapan PSAK No. 23 tentang pendapatan pada PT. Bintang Sayap Utama Cabang Indonesia Timur di Kota Manado - Supardi, Rendi Yehezkiel; Morasa, Jenny; Lambey, Robert (Universitas Sam Ratulangi, 2019)
Revenue increases the value of assets of a company's operational activities in accordance with applicable accounting principles. This guideline is a Statement of Accounting Standards (SFAS) No. 23 about income. In PSAK 23 there is a discussion on the recognition, measurement and disclosure of income that must be applied in accordance with the type and condition of the company. This study discusses the recognition and measurement of income from PT. Bintang Sayap Utama. This study uses descriptive qualitative by comparing the principles of recognition and measurement of income in PSAK 23 with the application by the company. The results of interviews and reviews of the company's financial statements indicate that the company has applied the concept of PSAK 23 on sales and income as well as on the price difference but not onÂ the interest of income and other income. Based on this analysis, the application of recognition is revealed and the measurement of income at PT. Bintang Sayap Utama is not in accordance with PSAK 23 and it has been suggested to make corrections to the recording in which have found to not be appropriate.